2022
DOI: 10.3390/genes13030456
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of Alternative Splicing and Gene Fusion during Rice Black-Streaked Dwarf Virus Stress in Maize (Zea mays L.)

Abstract: Rice black-streaked dwarf virus (RBSDV) causes maize rough dwarf disease (MRDD), which is a viral disease that significantly affects maize yields worldwide. Plants tolerate stress through transcriptional reprogramming at the alternative splicing (AS), transcriptional, and fusion gene (FG) levels. However, it is unclear whether and how AS and FG interfere with transcriptional reprogramming in MRDD. In this study, we performed global profiling of AS and FG on maize response to RBSDV and compared it with transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In the Oryza genus, the O. japonica genome had more fusion genes compared to O. indica, O. barthii and O. glaberrima (Zhou et al, 2022b) whereas differential gene fusions were observed among different Papaver species affecting alkaloid concentration (Catania et al, 2022). However, the gene fusions reported in sesame, particularly in Swetha are much higher than in maize (Zhou et al, 2022a) and Oryza (Zhou et al, 2022b). The duplication of parental genes prior to fusion was evident also in the sesame genome (Zhou et al, 2022b) while most of the added domains were products of horizontal transfer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the Oryza genus, the O. japonica genome had more fusion genes compared to O. indica, O. barthii and O. glaberrima (Zhou et al, 2022b) whereas differential gene fusions were observed among different Papaver species affecting alkaloid concentration (Catania et al, 2022). However, the gene fusions reported in sesame, particularly in Swetha are much higher than in maize (Zhou et al, 2022a) and Oryza (Zhou et al, 2022b). The duplication of parental genes prior to fusion was evident also in the sesame genome (Zhou et al, 2022b) while most of the added domains were products of horizontal transfer.…”
Section: Discussionmentioning
confidence: 97%
“…In higher plant genomes gene fusion is a complex process with a poorly understood evolutionary mechanism. Gene fusion events have been reported in the biosynthesis of alkaloids in opium poppy (Catania et al, 2022), viral infection in maize (Zhou et al, 2022a) and in the evolution of new genes in the genus Oryza (Zhou et al, 2022b). In the sesame pan-genome, 2.3% of AP2/ERF genes and 10% of WRKY genes were products of gene fusion.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, changes in AS substantially identified sugarcane mosaic virus‐induced proteomic changes in sugarcane (Du et al, 2020). Furthermore, AS‐mediated transcriptional regulation is essential in resistance to RBSDV infection in maize (Zhou et al, 2022).…”
Section: Plant Viruses and Effects On Host Alternative Splicingmentioning
confidence: 99%
“…Genome‐wide variable splicing dynamics occur during plant virus infection, filling a knowledge gap (Mandadi & Scholthof, 2015). To date, AS has been studied to a lesser extent in plant virus diseases, such as MRDV caused by RBSDV (Zhou et al, 2022).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation